2020
DOI: 10.4047/jap.2020.12.5.265
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on hydrothermal degradation of cubic-containing translucent zirconia

Abstract: PURPOSE The aims of this study were to investigate mechanical properties and hydrothermal degradation behaviour of the cubic-containing translucent yttrium oxide stabilized tetragonal zirconia polycrystal (Y-TZP). MATERIALS AND METHODS Four groups of Y-TZP (T, ST, XT, and P), containing different amount of cubic crystal, were examined. Specimens were aged by autoclaving at 122℃ under 2 bar pressure for 8 h. Phase transformation was analyzed using X-ray diffraction (XRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…LTD may also be another reason for the significantly lower fracture resistance values of the NP-treated tetragonal (IC and LP) and cubic SC zirconia restorations. Kengtanyakich and Peampring [33] investigated the mechanical properties and hydrothermal degradation of disk-shaped 3Y-TZP and cubic zirconia materials. They found that cubic zirconia had lower fracture hardness and flexural strength than 3Y-TZP before aging.…”
Section: Discussionmentioning
confidence: 99%
“…LTD may also be another reason for the significantly lower fracture resistance values of the NP-treated tetragonal (IC and LP) and cubic SC zirconia restorations. Kengtanyakich and Peampring [33] investigated the mechanical properties and hydrothermal degradation of disk-shaped 3Y-TZP and cubic zirconia materials. They found that cubic zirconia had lower fracture hardness and flexural strength than 3Y-TZP before aging.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the average grain size for group XT was 1.57 µm which was larger than the group T and ST. Group P had the largest grain sizes of 2.28 µm. 7 Therefore, larger grain sizes of group XT and P might contribute to lower mechanical strength compared with smaller grains of group T and ST due to the dislocation on the crystal grain boundaries under dynamic or fatigue assessment affecting the transposition of the stimuli from grain to grain. 19,20 The strength in present results was higher than a previous study which evaluated the flexural fatigue strength of 3Y- TZP, 4Y-PSZ, and 5Y-PSZ on a 3-point bend test for 6,000 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrothermal aging simulation was set up using an autoclave oven (TOMY ES 215/ES-315, TOMY Kogyo) at 122°C under pressure of 2 atm for 8 hours. 10 Each specimen was sealed in a sterilization pack and placed in the autoclave. After aging, all specimens were air-dried for 24 hours before testing.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Cubic crystal is the most stable phase structure; therefore, mechanical properties of cubic-containing zirconia seem to be stable after being hydrothermally aged. 10 Even though cubic-containing zirconia (4Y-TZP and 5Y-TZP) is proved to resist to hydrothermal aging, some tetragonal crystals presenting in 4Y-TZP and 5Y-TZP are prone to be transformed to monoclinic phase spontaneously after being immersed in water in long-term period especially at the zirconia surfaces. Also, there is little evidence showing that the translucency of cubic-containing zirconia is stable after aging.…”
Section: Introductionmentioning
confidence: 99%